MODEL CUPs BERBANTUAN PhET UNTUK MEREMEDIASI MISKONSEPSI GETARAN HARMONIS SMAN 1 SUNGAI RAYA - Ghalih Prasetyo; Edy Tandililing; Syukran Mursyid (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstracthitung This study aimed to determine the effectiveness of the application of CUPS learning model assisted by PhET simulations to reduce the learners’ misconceptions on a harmonic osilation at SMAN 1 Sungai Raya. This study was conducted through an experimental study in the form of pre-experimental design by one group pre-test post- test design with a total sample of 23 students in class X MIA 4. The instrument used in this study was a diagnostic test which consists of 10 multiple-choice questions in the form of open ground. From the calculation of the result of pretest and posttest data, there was a reduction number of learners who had misconceptions (average∆S= 57.75%) after remediation with CUPS learning model assisted by PhET simulations. Based on the analysis using the McNemar test, there was a significant conceptual change occurred (32          = 15.27; df = 1; α = 5%) after remediation with CUPSlearning model assisted by PhET simulations. The application of CUPS learning model assisted by PhET simulations were effective in decreasing the learners’ misconceptions with high category (O = 6,75). This research hopefully can be used as an alternative way to reduce the number of learners’ misconceptions in learning activities.Keyword: Conceptual Understanding Procedures, Harmonic Oscillation, Misconceptions